(untitled) (Educational Perspectives Magazine (REPED), 2023)
The initial formation of the infants educators becomes relevant having as a starting point the governmental policies being used at the present time as an attempt to meet the social needs. Globalisation, technological achievements, the technological of neurosciences and psychology plus the increasing in the number of women in the working field allows us lo visualizo a child with many needs, a child with different skills and characteristics represenl a huge challenge for the educators at pre-school levels. The curricula of the nursery school teachers being formed at universities participating in the “Consejo de Rectores”, gives us a visión of the kind of professional we are looking to mold in order to respond to t he needs of our society.